2012
DOI: 10.1108/09564231211248453
|View full text |Cite
|
Sign up to set email alerts
|

Customer experience modeling: from customer experience to service design

Abstract: Purpose -Customer experience has become increasingly important for service organizations that see it as a source of sustainable competitive advantage, and for service designers, who consider it fundamental to any service design project. Design/methodology/approach -Integrating contributions from different fields, CEM was conceptually developed to represent the different aspects of customer experience in a holistic diagrammatic representation. CEM was further developed with an application to a multimedia servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(205 citation statements)
references
References 30 publications
4
196
0
5
Order By: Relevance
“…On the other hand, greater connectivity allows consumers to have customised access to information, select only products and services matching their needs, and thus avoid any problem related to the excess of information (Pantano, 2014). Furthermore, these systems allow both consumers and retailers to easily communicate with each other, share comments on products and services, and collaborate in the creation of the service (highly facilitated by self-service systems) (Teixeira et al, 2012;Veryzer and Borja de Mozota, 2005). As a consequence, these systems also affect the way consumers interact with sellers and retailers (Gustafsson et al, 2012;Ko and Kincade, 2007;Leitner and Gretchenig, 2009;Wood and Reynolds, 2013).…”
Section: Smart Retailing Versus Traditional Technology Management Appmentioning
confidence: 99%
“…On the other hand, greater connectivity allows consumers to have customised access to information, select only products and services matching their needs, and thus avoid any problem related to the excess of information (Pantano, 2014). Furthermore, these systems allow both consumers and retailers to easily communicate with each other, share comments on products and services, and collaborate in the creation of the service (highly facilitated by self-service systems) (Teixeira et al, 2012;Veryzer and Borja de Mozota, 2005). As a consequence, these systems also affect the way consumers interact with sellers and retailers (Gustafsson et al, 2012;Ko and Kincade, 2007;Leitner and Gretchenig, 2009;Wood and Reynolds, 2013).…”
Section: Smart Retailing Versus Traditional Technology Management Appmentioning
confidence: 99%
“…Teixeira et al, 2012), it is noteworthy that the analyses reported in the reviewed papers typically concern experiences that are common or typical rather than individual or subjective (e.g. Baranova et al, 2011;Clatworthy, 2010;Huang et al, 2012;Johns and Clark, 1993;Mangiaracina et al, 2009;Rasila et al, 2009) based on data gathered at the level of individual customers and some, such as Crosier and Handford (2012), also report on example qualitative data from individual customers.…”
Section: Customer Journeys To Investigate and Communicate Common Expementioning
confidence: 99%
“…Through case studies with service providers, design agencies, and consulting firms, they found that experiential services often are designed through a customer journey approach, to strengthen the customer experience across the entire service process. Their work has been influential in service management research (Mahr et al, 2013;Patrício et al, 2011;Shaw and Williams, 2009;Tax et al, 2014;Teixeira et al, 2012).…”
mentioning
confidence: 99%
“…Nowadays marketing managers commonly agree that customer experience is the key strategy for the present and the future struggles in competitive environments, but this is a difficult strategy to execute (Bolton et al, 2014;Dirsehan & Yalçin, 2011;IBM, 2005;Nenonen, Rasila, Junnonen, & Kärnä, 2008;Tax, McCutcheon, & Wilkinson, 2013;Teixeira, Nunes, Nóbrega, Fisk, & Constantine, 2012). The biggest challenge in creating an excellent customer experience does not lie in creating single excellent touch-points, but rather in creating a link among them, so that they result from a general design and consistent framework (Rawson et al, 2013).…”
Section: Mapping the Customer Journeymentioning
confidence: 99%